Análise de eficiência dos gastos públicos em educação no município de Meruoca - Aguiar Neto, João Coutinho (2010)
The aim of this study is to evaluate the quality of public spending on education in the city of Meruoca. It uses non-parametric methodology of DEA (Data Envelopment Analysis - DEA) to estimate levels of efficiency, whereas indicators of input and product and elementary education for all municipalities in Ceara. Thus, it will generate robust rankings of efficiency that enables you to check which places the city of Meruoca. In order to contextualize the analysis of efficiency, are also considered major programs that affect spending on education and the state of Ceará is analyzed descriptive characteristics and management in education Meruoca. The results of this study point to an efficient management of education in the municipality of Meruoca, especially in early childhood education.